TASK IMPLEMENTATION OF BARTENDER IN MOLECULE GASTRO BAR NOVOTEL PEKANBARU CITY - Bimo Satrio Wibowo; Teguh Widodo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The research was conducted at Novotel Pekanbaru which aim to find out the task implementation of the bartender in the Molecule Gastro Bar. To carry out the task implementation, there are 3 stages. First, work before the bar is opened. Second, job when the bar is opened. Third, job when the bar is closed. The task implementation of the bartender in the Molecule Gastro Bar Novotel Pekanbaru is working with Standard Operational Procedure to make the work of the bartenders is easy to serve guest. Molecule Gastro Bar at Novotel pekanbaru is the one of the outlet who is giving the financial benefits to hotels. To carry out the task implementation of the bartender must need to understanding about bar, starts from the type of drink, how to present and serve and mixology techniques that will be provided to the guest. The research uses qualitative methods and to get the data the author uses interview, observation, and documentation. From the results of the research that the author did, the results show that the task implementation of the bartender’s tasks can run well. Keywords: Task Implementation, Bartender.